\(\Rightarrow x^3+27-x^3+4x=15\\ \Rightarrow4x=-12\Rightarrow x=-3\)
\(\Rightarrow x^3+27-x^3+4x=15\\ \Rightarrow4x=-12\Rightarrow x=-3\)
Tìm x biết:
a) ( x – 3 ) 3 – ( x – 3 ) ( x 2 + 3 x + 9 ) + 9 ( x + 1 ) 2 = 15;
b) x(x – 5)(x + 5) – (x + 2)( x 2 - 2x + 4) = 3.
tìm x, biết:
a) x2-2x+1=25
b) (5x+1)2-(5x-3)(5x+3)=30
c) (x-1)(x2+x+1)-x(x+2)(x-2)=5
d) (x-2)3-(x-3)(x2+3x+9)+6(x+1)2=15
tìm x biết:
a) x2-2x+1=25
b) (5x+1)2-(5x-3)(5x+3)=30
c) (x-1)(x2+x+1)-x(x+2)(x-2)=5
d) (x-2)3-(x-3)(x2+3x+9)+6(x+1)2=15
Bài 1: Tìm x:
1) (x-3)3 -( x-3)(x2+ 3x+9) +6( x+1)2+ 3x2 = -33
2) (X-3)( X2+ 3X+9) - X(X-2)( 2+X) = 1
3) (X+2)(X2 - 2X+4) – X(X-3)(X+3) = 26
Tìm x :
a) x (3x + 1) + (x -1)2 - (2x + 1)(2x -1) = 0
b) (x + 1)3 + (2 - x)3 - 9(x - 3)(x+3) = 0
c) (x - 1)3 - (x + 3)(x2 - 3x + 9) + 3x2 = 25
d) (x + 2)3 - ( x +1)(x2 - x + 1) - 6(x - 1)2 = 23
e) (x + 3)(x2 - 3x + 9) - x(x - 2)(x+2) + 11 = 0
f) x(x - 3) - x + 3 = 0
1/Rút gọn các biểu thức: a)(x+1)2-(x-1)2-3(x+1)(x-1)
b)5(x+2)(x-2)-(2x-3)2-x2+17
c)(x-3)3-(x-3)(x2+3x+9)+6(x+1)2
2/ Tìm x a) (x+4)2-(x+1)(x-1)=16
b) (x+2)(x2-2x+4)-x(x2+2)=15
Bài 3.Tìm x biết
b) 3x( x2 + 4) –2x2 -8 =0
a) x2+5x =0
c) (x-3) (x2 + 3x +9) +x( x+2) (2- x) =36
C= 2x / x-3 - 3x+9/ x2 - 9
D= (15-x/ x2 - 25 + 2/ x+5 ) : x + 1/ x - 5
Bài 2: (2 điểm) Tìm x, biết:
a) (3x + 4)2 – (3x – 1)(3x + 1) = 49
b) x2 – 4x + 4 = 9(x – 2)
c) x2 – 25 = 3x - 15
d) (x – 1)3 + 3(x + 1)2 = (x2 – 2x + 4)(x + 2)